2012
DOI: 10.1007/s10856-012-4587-5
|View full text |Cite
|
Sign up to set email alerts
|

Thromboresistant and endothelialization effects of dopamine-mediated heparin coating on a stent material surface

Abstract: Heparinization of surfaces has proven a successful strategy to prevent thrombus formation. Inspired by the composition of adhesive proteins in mussels, the authors used dopamine to immobilize heparin on a stent surface. This study aimed to assess the thromboresistant and endothelialization effects of dopamine-mediated heparin (HPM) coating on a stent material surface. The HPM was synthesized by bonding dopamine and heparin chemically. Cobalt-chromium (Co-Cr) alloy disks were first placed in the HPM solution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…As a simple, versatile, and effective strategy to promote cell adhesion onto substrates with various material type and shape under solvent-free and non-toxic condition, polydopamine (PDA) films has attracted much attention in the field of biomaterials surface modification since Lee et al reported it in 2007 [41] . In the field of vascular biomaterials, PDA coating has been used as an immobilization layer for vascular endothelial growth factor (VEGF) [42,43] , heparin [44,45] , etc., and has also been used to control cell behaviors directly on the surface, which demonstrated that human umbilical vein endothelial cells (HUVECs) could adhere well and spread with a high viability on PDA coating [46][47][48] ; moreover, it showed that PDA coating on 316L stainless steel stent decreased adhesion and proliferation [48] .…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…As a simple, versatile, and effective strategy to promote cell adhesion onto substrates with various material type and shape under solvent-free and non-toxic condition, polydopamine (PDA) films has attracted much attention in the field of biomaterials surface modification since Lee et al reported it in 2007 [41] . In the field of vascular biomaterials, PDA coating has been used as an immobilization layer for vascular endothelial growth factor (VEGF) [42,43] , heparin [44,45] , etc., and has also been used to control cell behaviors directly on the surface, which demonstrated that human umbilical vein endothelial cells (HUVECs) could adhere well and spread with a high viability on PDA coating [46][47][48] ; moreover, it showed that PDA coating on 316L stainless steel stent decreased adhesion and proliferation [48] .…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…8,[18][19][20][21] In our in vitro study, endothelial cell adhesion was shown on the surface of the bare metal and albumin-coated stents, whereas the heparin coating seems not to promote cell adhesion. Compared with the in vivo situation, our endothelialization experiments were performed in an isolated system containing endothelial cells and cell culture media with 2% fetal calf serum.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study used dopamine to immobilized heparin on a stent surface showed thromboresistant and endothelialization effects in rabbit iliac artery restenosis model 26. And a TiO 2 and nitrogen doped-TiO 2 thin film was deposited by plasma enhanced chemical vapor deposition (PECVD) process and its applicability as a drug coating matrix was demonstrated in promising alternatives to polymer for the preparation of drug-eluting stents 27,28.…”
Section: Discussionmentioning
confidence: 99%